Etiology, Pattern, Treatment and Outcome of Maxillofacial Fractures at Dhulikhel Hospital - Chaurasia, N. K.; Upadhyaya, C.; Dulal, S. (Kathmandu University Medical Journal, 2021)
Background Maxillo-Facial region is one of the prominent parts of human body and is more vulnerable to injury when any form of trauma is encountered. Injury to this region can result in fractures and pattern of fractures often depends upon the mechanism of injury as well as direction of impact. Objective To determine the etiology, pattern, treatment, and outcome of maxillofacial fractures presenting to Dhulikhel hospital. Method The records of all the patients with maxillofacial injuries presenting to the department of oral and maxillofacial surgery of dhulikhel hospital between period of December 2012 to November 2019 were included in the study. The data regarding age, sex and etiology were recorded. The etiologies were classified as Motor vehicle accidents (MVA), interpersonal violence, fall injuries, sports related injuries, occupational hazards, gunshot injuries and animal attacks and others. Similarly, the pattern of fractures was recorded according to classification by anatomical site. The types of treatment performed was also recorded. Treatment outcome in the form of any postoperative complications were recorded. Result Out of 1366 patients with maxillofacial injuries, 378(27.7%) patients had fracture of maxillofacial region. The most common etiology was motor vehicle accidents (53.7%) followed by fall injury (31.2%). Zygomatico-maxillary complex was the most common type of fracture (27.9%). Open reduction and internal fixation were the most common form of treatment provided (85.4%) and post-operative complications were minimal (5.0%). Conclusion Motor vehicle accidents still remain the most common cause of maxillofacial fractures. Midface fractures are more common than mandible fracture. The present study provides an insight into changing etiology and pattern of maxillofacial fractures and open reduction and internal fixation remains the most favored treatment of maxillofacial fractures with minimum complications.